Prospects of use of vegetable raw materials in the technology of sour-milk dessert - Bandura (Kuzmyk), Uliana; Marynin, Andriy; Sviatnenko, Roman; Zheludenko, Julia; Kurmach, Mykhailo; Shvaiko, Roman (My University, 2021)
Prospects for the use of vegetable raw materials in the technology of sour-milk desserts have been substantiated. According to the results of organoleptic and physicochemical parameters, a rational ratio of recipe components in the product has been established.The results of the organoleptic evaluation show that the introduction of sublimated fruits in an amount of less than 5 % does not give a pronounced taste and smell. And the introduction of dry whey protein concentrate in an amount of more than 6 % contrib-utes to a heterogeneous consistency with the presence of lumps.It has been investigated, that with increasing the amount of sublimated fruits in the sour-milk dessert, the active acidity slowly decreased in the range of 4.8...5.4 pH units. Due to which the process of fermentation of the mixture is slow. The moisture holding index increased with the addition of sublimated fruits by an average of 4 %. The presence of a dry whey protein concentrate gives the products a delicate plastic consistency due to the high dispersion of whey protein micelles and the peculiarities of gelation.Therefore, it is recommended to add sublimated fruits to the sour-milk dessert not more than 7 %, dry whey protein concen-trate not more than 6 %.The nutritional value of the sour-milk dessert in accordance with the most important components according to the daily requirement has been studied. The consumption of sour-milk dessert will ensure the content of easily digestible biologically com-plete milk protein within 5–8 g/100 g. The combination of the sour-milk base with raw fruits will provide potassium content by 166–267 g/100 g, magnesium content by 16–24 g/100 g, calcium by 135–180 g/100 g, sodium by 53–70 g/100 g.
Keywords: dessert; freeze-dried fruits; проблемна науково-дослідна лабораторія; десерт кисломолочний; сублімовані фрукти; сублімовані фрукти